2018
DOI: 10.6026/97320630014132
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the Molecular Modelling and Docking Analysis of AIF-NLS complex to infer Nuclear Translocation of the Protein

Abstract: Apoptosis Inducing Factor protein has a dual role depending on its localization in mitochondrion (energy production) and nucleus (induces apoptosis). Cell damage transports this protein to nucleus which otherwise favors mitochondrion. The alteration of Nuclear Localisation Signal tags could aid nuclear translocation. In this study, apoptosis inducing factor protein (AIF) was conjugated with strong NLS tags and its binding affinity with Importin was studied using in silico approaches such as molecular modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In contrast, AIF lacking MLS can spontaneously bind FAD and refold into mature AIF with a potential apoptosis-promoting function [ 4 , 8 ]. Normally, AIF performs mitochondrial functions and translocates to the nucleus only under the induction of apoptotic signals [ 33 ]. Once DNA damage occurs, the permeability of the mitochondrial outer membrane changes, and AIF is released from mitochondria [ 4 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, AIF lacking MLS can spontaneously bind FAD and refold into mature AIF with a potential apoptosis-promoting function [ 4 , 8 ]. Normally, AIF performs mitochondrial functions and translocates to the nucleus only under the induction of apoptotic signals [ 33 ]. Once DNA damage occurs, the permeability of the mitochondrial outer membrane changes, and AIF is released from mitochondria [ 4 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normally, AIF performs mitochondrial functions and translocates to the nucleus only under the induction of apoptotic signals [ 33 ]. Once DNA damage occurs, the permeability of the mitochondrial outer membrane changes, and AIF is released from mitochondria [ 4 , 33 ]. However, subcellular localization experiments indicated that most Hl AIF-2 was localized in both the cytoplasm and nucleus of HEK293T cells without Cd 2+ treatment ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%